Data Mining and Business Intelligence. - Hota, Jyotiranjan. (BPB Publications, 2025)
Data mining is crucial in business intelligence as it enables organizations to extract valuable insights and patterns from vast datasets, ultimately supporting informed decision-making, enhancing operational efficiency, and driving strategic growth. Validations, model building and interpretations are accomplished through databases, data warehouses, various supervised and unsupervised algorithms, tools for data modeling, descriptive analytics, diagnostic analytics, predictive analytics and prescriptive analytics to ensure accurate decision-making.